Selective Autophagy of Peroxisomes in Plants: From Housekeeping to Development and Stress Responses - Olmedilla, Adela; Sandalio, Luisa M. (Frontiers in Plant Science, 2019)
Peroxisomes are dynamic organelles involved in multiple functions including oxygen and nitrogen reactive species metabolism. In plants, these organelles have a close relationship with chloroplasts and mitochondria characterized by intense metabolic activity and signal transduction. Peroxisomes undergo rapid changes in size, morphology and abundance depending on the plant development stage and environmental conditions. As they are not only essential for redox homeostasis but also for sensing stress, signalling transduction and cell survival, their formation and degradation need to be rigorously regulated. In this review, new insights into the regulation of plant peroxisomes are briefly described, with a particular emphasis on pexophagy components and their regulation.